Implementation Of The Diversion Method For Children In Confrontation With The Law In Child Criminal Judgment Process - Miranda Dalimunthe; Ira Alia Maerani (UNISSULA Semarang, 2021)
The purpose of this paper is to find out, examine and analyze the procedural diversion for children in conflict with the law in the Juvenile Criminal Justice System.In this paper the author uses a normative juridical method. In the conclusion of the discussion, children in conflict with the law are considered as legal subjects who are not yet competent and cannot understand what they are doing. Investigation of children's cases is carried out by investigators determined by the Decree of the Head of the State Police of the Republic of Indonesia or other officials appointed by the Head of the State Police of the Republic of Indonesia. If the Diversion is successful in reaching an agreement, the Investigator will submit the Minutes of the Diversion along with the Diversion Agreement to the head of the district court for a determination to be made. On the other hand, if the Diversion process fails, the Investigator is obliged to continue the investigation and delegate the case to the Public Prosecutor by attaching the Diversion Report and the community research report. Children who are arrested must be deposited in the LPKS. The cost for each child placed in LPKS is charged to the budget of the ministry that carries out government affairs in the social sector.